2020
DOI: 10.3390/nu12051308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prunus cerasus L. Seeds and Juice on Liver Steatosis in an Animal Model of Diet-Induced Obesity

Abstract: The accumulation of adipose tissue increases the risk of several diseases. The fruits-intake, containing phytochemicals, is inversely correlated with their development. This study evaluated the effects of anthocyanin-rich tart cherries in diet-induced obese (DIO) rats. DIO rats were exposed to a high-fat diet with the supplementation of tart cherry seeds powder (DS) and seed powder plus juice (DJS). After 17 weeks, the DIO rats showed an increase of body weight, glycaemia, insulin, and systolic blood pressure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 68 publications
4
26
0
Order By: Relevance
“…The anti-inflammatory effects, induced particularly by tart cherry seeds, were not related to the body and VAT weight modulations. The changes of glycemia levels, the decrease of oxidative stress, and the downregulation of leptin in VAT [ 61 , 62 ], induced by tart cherry supplementation, could explain the anti-inflammatory effects observed in this study. Down regulation of leptin contributes to insulin resistance and show a correlation to the risk of metabolic syndrome, and leptin modulate immune reactions [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The anti-inflammatory effects, induced particularly by tart cherry seeds, were not related to the body and VAT weight modulations. The changes of glycemia levels, the decrease of oxidative stress, and the downregulation of leptin in VAT [ 61 , 62 ], induced by tart cherry supplementation, could explain the anti-inflammatory effects observed in this study. Down regulation of leptin contributes to insulin resistance and show a correlation to the risk of metabolic syndrome, and leptin modulate immune reactions [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 86%
“…At the same time, the increase of adipokines consequent to HFD correlates with the degree of oxidative stress, with a reduction of superoxide dismutase activity [ 65 ]. As previously demonstrated, tart cherry supplementation can reduce the oxidative stress [ 61 ] and to modulate the levels of adipokines [ 62 ]. This could explain the anti-inflammatory effects at the level of VAT and, in particular, in the perigonadal depots.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study demonstrated in obese subjects, as individuals at risk for chronic metabolic inflammation, a significant reduction in pro-inflammatory MCP-1, a trend for reduction of TNF-α, a decrease of 5% of erythrocyte sedimentation rate (ESR) after consumption of tart cherry juice for four weeks [ 72 ]. Recently, in preclinical studies in rats with diet-induced obesity (DIO), the supplementation of tart cherry juice and seeds reduced the neuroinflammatory process, liver steatosis, inflammation, and adipose gene transcription in visceral adipose tissue [ 73 , 74 , 75 , 76 ].…”
Section: Therapeutical Strategiesmentioning
confidence: 99%
“…Sour cherry is cultivated for its sharp and juicy fruits that are mostly destined to produce foods like jam, jelly, and syrup or alcohol beverages such as wine, brandy, and fruit beer [ 1 , 4 ]. The current research suggests that intake of fresh sour cherry berries or juice promotes health due to the positive action of anthocyanins and phenolic compounds [ 3 , 5 ]. The consumption of cherries may reduce the risk of arthritis, cancer, cardiovascular disease, and diabetes, and may improve sleep and cognitive functions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%